Pengaruh Skala Usaha,Umur Usaha dan Omset Usaha terhadap Penerapan Sistem Informasi Akuntansi pada Umkm di Kecamatan Paal Merah Kota Jambi - Umi Harti; Youdhi Prayogo; Muhamad Subhan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstrack This research method is descriptive quantitative research. The population in this research is MSMEs in Paal Merah District, Jambi City, in 2022 there will be 7,591 MSME units. The number of samples in this study was 99 respondents. The sample determination in this research was carried out using simple random sampling. The results of the research are that the t-count value for business scale is 6.852 compared to the t-table value of 1.661, or t-count >t-table and the significance of the p-value is 0.001<0.05, so business scale has a significant effect on the implementation of accounting information systems . The t-calculated value of business age is 6.211 compared to the t-table value of 1.661 or t-count > t-table and the significance of the p-value is 0.001<0.05, so business age has a significant effect on the implementation of the accounting information system. The t-count value of business turnover is 9.576 compared to the t-table value of 1.661 or t-count >t-table and the significance of the p-value is 0.001<0.05, so business turnover has a significant effect on the implementation of the accounting information system. Fcount is 106.412 by comparing Ftable ɑ =0.05 with numerator degree 3, and denominator degree of freedom 95, we get Ftable 2.700, so the Fcount value is greater than Ftable (106.412>2.700) and the significance value is 0.001<0.05 (alpha) so Business scale, business age, business turnover simultaneously influence the application of accounting information systems. Keywords: Scale, Age, and Business Turnover